Clinical, Immunological, and Genetic Features in 49 Patients With ZAP-70 Deficiency: A Systematic Review - Sharifinejad, Niusha; Jamee, Mahnaz; Zaki-Dizaji, Majid; Lo, Bernice; Shaghaghi, Mohammadreza; Mohammadi, Hamed; Jadidi-Niaragh, Farhad; Shaghaghi, Shiva; Yazdani, Reza; Abolhassani, Hassan; Aghamohammadi, Asghar; Azizi, Gholamreza (Frontiers in Immunology, 2020)
Background: Zeta-Chain Associated Protein Kinase 70 kDa (ZAP-70) deficiency is a rare combined immunodeficiency (CID) caused by recessive homozygous/compound heterozygous loss-of-function mutations in the ZAP70 gene. Patients with ZAP-70 deficiency present with a variety of clinical manifestations, particularly recurrent respiratory infections and cutaneous involvements. Therefore, a systematic review of ZAP-70 deficiency is helpful to achieve a comprehensive view of this disease. Methods: We searched PubMed, Web of Science, and Scopus databases for all reported ZAP-70 deficient patients and screened against the described eligibility criteria. A total of 49 ZAP-70 deficient patients were identified from 33 articles. For all patients, demographic, clinical, immunologic, and molecular data were collected. Results: ZAP-70 deficient patients have been reported in the literature with a broad spectrum of clinical manifestations including recurrent respiratory infections (81.8%), cutaneous involvement (57.9%), lymphoproliferation (32.4%), autoimmunity (19.4%), enteropathy (18.4%), and increased risk of malignancies (8.1%). The predominant immunologic phenotype was low CD8+ T cell counts (97.9%). Immunologic profiling showed defective antibody production (57%) and decreased lymphocyte responses to mitogenic stimuli such as phytohemagglutinin (PHA) (95%). Mutations of the ZAP70 gene were located throughout the gene, and there was no mutational hotspot. However, most of the mutations were located in the kinase domain. Hematopoietic stem cell transplantation (HSCT) was applied as the major curative treatment in 25 (51%) of the patients, 18 patients survived transplantation, while two patients died and three required a second transplant in order to achieve full remission. Conclusion: Newborns with consanguineous parents, positive family history of CID, and low CD8+ T cell counts should be considered for ZAP-70 deficiency screening, since early diagnosis and treatment with HSCT can lead to a more favorable outcome. Based on the current evidence, there is no genotype-phenotype correlation in ZAP-70 deficient patients.